COVID-19 and social protection in the Gulf Region: Analysis and lessons learned on shock-responsive and child-sensitive systems - Maya Hammad (International Policy Centre for Inclusive Growth (IPC-IG), 2022)
The COVID-19 pandemic has severely impacted the global and each national economy, and also people's well-being and individual livelihoods. Vulnerable groups have been hit particularly hard, given their often precarious and dependent financial situation coupled with inadequate social protection coverage. The fuel-exporting countries of the Gulf Cooperation Council (GCC) experienced the pandemic as a 'double crisis', as lockdown measures and a halt in business operations coincided with a significant drop in oil prices. This Research Report report seeks to answer several questions about the social protection responses to COVID-19 of four countries in the GCC: Bahrain, Kuwait, Saudi Arabia and the United Arab Emirates (UAE).
Keywords: 330; social protection; COVID-19; GCC